Role of Roads and Irrigation on Food Security in Indonesia - Oktiani, Erlisa; Khoirunurrofik, Khoirunurrofik (Economics Development Analysis Journal, 2024)
Food security is a critical aspect of assessing people's well-being. One key factor influencing food security is infrastructure. In Indonesia, food security varies significantly, but it has remained stagnant at lower levels in the eastern regions for several years. According to regulations governing financial relations between the central and regional levels, spending on public service infrastructure should constitute 40% of the regional budget. This study examined the relationship between road infrastructure and food security. However, the study also considers irrigation development and other variables for a more comprehensive analysis. By analyzing data from 508 regencies and cities in Indonesia from 2018 to 2021, this research explores the impact of road and irrigation infrastructure on food security at the local level. The study, utilizing the Generalized Method of Moments (GMM), concludes that consistent road construction can improve food security in regencies and cities across Indonesia. Gross Regional Domestic Product (GRDP), access to sanitation, and water availability also play crucial roles in determining national food security.